Hydroxypropyl‐β‐cyclodextrin encapsulated stationary phase based on silica monolith particles for enantioseparation in liquid chromatography. Issue 3 (17th December 2020) - Lu, Yao; Sun, Genlin
Abstract: Hydroxypropyl‐β‐cyclodextrin‐encapsulated stationary phase incorporated on silica monolith particles was prepared by physical embedding, providing a new method for the development of chiral stationary phase for enantioseparation in liquid chromatography. Ground silica monolith particles of about 2.0 μm were prepared via sol–gel reaction followed by differential sedimentation. Initially, the silica monolith particles were pretreated with 3‐trimethoxysilyl propyl methacrylate to attach double‐bonded ligands onto the surface, then a network structure was formed onto the surface of the particle using N ‐isopropyl acrylamide as functional monomer. Hydroxypropyl‐β‐cyclodextrin was encapsulated inside N ‐isopropyl acrylamide copolymerized layer on the surface of silica monolith particles. The effect of the amount of chiral selector on the chromatographic efficiency of the chiral stationary phase was examined. The glass lined stainless steel columns (1 mm internal diameter, 300 mm length) were packed with the stationary phase for estimation of the efficiency by separation of phenylsuccinic acid, oxybutynin, equol, and naproxen enantiomers in high‐performance liquid chromatography, with the resolutions of 1.54, 1.72, 2.54, and 2.31, respectively. The column to column repeatabilities through relative standard deviation were found better than 3%. The experimental results indicate that the sol‐gel ground silica particles modified with β‐cyclodextrin provide a promising way for the separation of chiral enantiomers.